Appropriate prescribing of azithromycin for community‐acquired pneumonia. Issue 6 (24th May 2022) - Qian, Sue; Siu, Johnny; Hussein, Abbas; Zheng, Yizhong
Abstract: Azithromycin is prescribed for atypical antimicrobial cover in severe community‐acquired pneumonia. Inappropriate azithromycin administration incurs unnecessary financial costs, exacerbates antimicrobial resistance and risks QTc interval prolongation leading to cardiac arrhythmias. The present study demonstrated that a majority of patients were prescribed azithromycin without having electrocardiograms to assess the QTc interval and without meeting criteria for severe community‐acquired pneumonia based on CURB‐65 score.